'Doing with …' rather than 'doing for …' older adults: rationale and content of the 'Stay Active at Home' programme. (November 2017) - Metzelthin, Silke F; Zijlstra, Gertrud AR; van Rossum, Erik; de Man-van Ginkel, Janneke M; Resnick, Barbara; Lewin, Gill; Parsons, Matthew; Kempen, Gertrudis IJM
Background: Owing to increasing age, accidents or periods of illness, home care services are provided to community-dwelling older adults. Traditionally, these services focus on doing things for older adults rather than with them; though from a rehabilitative perspective, it is important to assist older adults to attain and maintain their highest level of functioning. Consequently, a re-orientation of home care services is required away from treating disease and creating dependency towards focusing on capabilities and opportunities and maximising independence. To achieve this behavioural change in home care professionals, the 'Stay Active at Home' programme was developed. Aims and methods: The aim of this article is to give a detailed description of the rationale and content of the 'Stay Active at Home' programme by making use of the TIDieR (Template for Intervention Description and Replication) Checklist. Approach: 'Stay Active at Home' is a comprehensive training programme that aims to equip home care professionals (i.e. community nurses and domestic support workers) with the necessary knowledge, attitude, skills and social and organisational support to deliver day-to-day services at home from a more rehabilitative perspective. More specifically, home care professionals are expected to deliver goal-oriented, holistic and person-centred services focusing on supporting older adults to maintain, gain or restore their competences to engage in physical and daily activities so that they can manage their everyday life as independently as possible.